Rational organization of training a group of physical rehabilitation on the initial stage of training in universities - Marakushin, A.I.; Piddubnyi, A.G.; Tsymbalyuk, Z.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to justify a rational approach to organization of group sessions of physical rehabilitation at the initial stage of training in universities. Material: 217 students of groups of physical rehabilitation KhNEU named Simeon Kuznets were involved in the experiment. Results: the organizational difficulties of physical education classes in groups of physical rehabilitation at the beginning of the school year were examined. An effective way of determination of the level of students’ functional state was identified. The effectiveness of the formation of groups of physical rehabilitation at the initial stage of training was experimentally verified on base on the definition of students’ functional state and the content of this stage of training was determined. A reduction of the level of students’ functional state of physical rehabilitation groups at the beginning of studying (I semester) was stated. Conclusions: the proposed changes in the organization of students with disabilities in health status in the group by the level of functional status and the content of studying allowing students to preserve the functionality of the initial stage of studying.